THE EFFECT OF STRATEGIC MANAGEMENT AND LEARNING CREATIVITY ON LEARNING INNOVATION WITH SELF-EFFICACY AS A MODERATING VARIABLE IN ISLAMIC HIGHER EDUCATION - Muhammad Ihsan Mas’ud; Munirul Abidin (Jurnal Manajemen Pendidikan, 2026)
This study investigates the influence of strategic management and learning creativity on learning innovation, while evaluating the moderating role of self-efficacy within Islamic higher education institutions. Employing a quantitative survey method involving 166 students and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results demonstrate that strategic management, learning creativity, and self-efficacy significantly affect learning innovation directly. However, the analysis reveals that self-efficacy does not strengthen the relationship between learning creativity and learning innovation. Conversely, self-efficacy acts as a negative moderator in the relationship between strategic management and innovation. These findings suggest that learning innovation is predominantly driven by institutional strategies, creative competencies, and self-confidence as direct predictors. Furthermore, the negative moderation implies a substitution effect, where high self-efficacy may diminish the reliance on strategic management frameworks to drive innovation.